ENTREPRENEURIAL READINESS TO ADOPT AI IN DIGITAL MARKETING: A SYSTEMATIC REVIEW OF THE LITERATURE AND COMPARATIVE ANALYSIS BETWEEN DEVELOPED AND DEVELOPING COUNTRIES - Yohanes Gunawan Wibowo; Eko Budi Satoto; Avicena Rifananta (International Journal of Artificial Intelligence for Digital Marketing, 2026)
Objective: This research aims to map the development of global research, compare the characteristics of entrepreneurial readiness across country contexts, and formulate a more contextual conceptual framework of readiness. Method: The method used is a Systematic Literature Review with bibliometric and thematic analysis of publications for the 2021–2025 period which were selected using the PRISMA protocol. Results: The results of the study show a significant increase in the trend of publications and citations, the dominance of the contribution of developed countries in knowledge production, as well as differences in the quality of AI adoption. Entrepreneurs in developed countries are integrating AI strategically and systemically, while in developing countries adoption is still partial due to structural limitations, technological literacy, and data governance. Novelty: This study proposes the expansion of Change Readiness Theory through the dimensions of technology, strategic vision, ethical-social alignment, and data governance as the foundation of sustainable socio-technical readiness for digital marketing transformation.